2022
DOI: 10.1145/3528223.3530064
|View full text |Cite
|
Sign up to set email alerts
|

Affine body dynamics

Abstract: Simulating stiff materials in applications where deformations are either not significant or else can safely be ignored is a fundamental task across fields. Rigid body modeling has thus long remained a critical tool and is, by far, the most popular simulation strategy currently employed for modeling stiff solids. At the same time, rigid body methods continue to pose a number of well known challenges and trade-offs including intersections, instabilities, inaccuracies, and/or slow performances that grow with cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…As a consequence, friction forces might violate the Coulomb constraint and there are no guarantees concerning the principle of maximum dissipation [Erl17]. Alternatively, smoothing the velocity–force relation eliminates the discontinuous jump of the friction force and the resulting computational burden at stick–slip transitions [PRM19, GHZ*20, LFS*20, FLS*21, MEM*20, CLL*22, LKL*22]. Even though in most approaches, the amount of smoothing is parametrized and can be reduced to get a better approximation of the true velocity–force relation at the cost of less computational stability, the friction force at zero velocity is always null and thus, these models cannot exactly reproduce stiction [PRSV16, PRM19, LKL*22].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, friction forces might violate the Coulomb constraint and there are no guarantees concerning the principle of maximum dissipation [Erl17]. Alternatively, smoothing the velocity–force relation eliminates the discontinuous jump of the friction force and the resulting computational burden at stick–slip transitions [PRM19, GHZ*20, LFS*20, FLS*21, MEM*20, CLL*22, LKL*22]. Even though in most approaches, the amount of smoothing is parametrized and can be reduced to get a better approximation of the true velocity–force relation at the cost of less computational stability, the friction force at zero velocity is always null and thus, these models cannot exactly reproduce stiction [PRSV16, PRM19, LKL*22].…”
Section: Related Workmentioning
confidence: 99%
“…Alternatively, smoothing the velocity–force relation eliminates the discontinuous jump of the friction force and the resulting computational burden at stick–slip transitions [PRM19, GHZ*20, LFS*20, FLS*21, MEM*20, CLL*22, LKL*22]. Even though in most approaches, the amount of smoothing is parametrized and can be reduced to get a better approximation of the true velocity–force relation at the cost of less computational stability, the friction force at zero velocity is always null and thus, these models cannot exactly reproduce stiction [PRSV16, PRM19, LKL*22]. Some approaches model static friction as linear springs which pull contacts back together over multiple simulation steps [YN06, XZB14].…”
Section: Related Workmentioning
confidence: 99%
“…We note that, while our formulation has linear treatment of variables λi$$ {\lambda}_i $$s and normal∑λi$$ {\Sigma}_{\lambda_i} $$s it still requires a parabolic mesh. Alternate and efficient formulations for stiff materials exist, for cases where engineering accuracy is not desired 2 …”
Section: Numerical Examplesmentioning
confidence: 99%
“…(2) Simulation of rigid , stiff and inextensible systems. Like quasi‐incompressibility, stiff materials have been traditionally modeled by decomposing the deformation into a rotation and a stretch component and by penalising the latter part 2 . Intuitively, and as studies in rigid body dynamics have shown, simulating stiff materials poses the same challenge as that of incompressibility, since rigidifying a deformable system through large penalty terms eventually either blows up the numerical routine and/or the accuracy of secondary variables, which reflects in stresses remains oscillatory or at best poor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation